RSM-based optimization of recycled aggregate concrete with pozzolanic materials under high temperatures - Saqib Khan, Muhammad; Ulhaq, Aman; Mohammed Alsekait, Deema; Faisal Javed, Muhammad; Jameel, Mohammed; Alabduljabbar, Hisham; Abdelminaam, Diaa Salama (Frontiers in Materials, 2025)
The increasing demand for sustainable concrete has encouraged the use of recycled aggregates (RA), though their limited performance under elevated temperatures remains a key challenge. This study explores the use of supplementary cementitious materials (SCMs) to improve the thermal resistance of recycled aggregate concrete (RAC). Three concrete mixes containing 0%, 25%, and 50% RA were exposed to temperatures up to 600°C. The effects of incorporating 15% silica fume (SF) and 30% fly ash (FA) on residual compressive and tensile strengths were evaluated. Response Surface Methodology (RSM) was employed for experimental design and optimization, while analysis of variance (ANOVA) confirmed the statistical significance of key influencing factors, including temperature and SCM content. Results showed that SCMs improved tensile strength by up to 12% in RAC25 and helped retain strength at elevated temperatures, despite some reduction in compressive strength due to thermal stress. Among all mixes, RAC25 with SCMs showed the most balanced performance. The study highlights the potential of combining SCMs with RSM-based optimization to enhance the fire resistance of RAC. These findings contribute to the development of more durable, eco-efficient concrete materials, particularly for fire-prone or high-temperature environments, and support the advancement of sustainable construction practices.